Carbon material, carbon material dispersion composition, composite slurry, electrode film, secondary battery, and vehicle

By using multi-layer carbon nanotubes and fluororesin to prepare a dispersible carbon material composition, the problem of low wettability of carbon nanotubes is solved, and the high rate and cycle characteristics of secondary batteries are achieved, which are suitable for high-performance battery applications.

CN119585202APending Publication Date: 2025-03-07아티엔스가부시키가이샤 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380054630.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-24
Filing Date
2023-11-08
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The low wettability of existing carbon nanotubes in solvents makes it difficult to produce a dispersion composition with high concentration and excellent dispersion stability, which limits its application in secondary batteries.

Method used

Using a carbon material containing multi-layer carbon nanotubes, the BET specific surface area and diffraction peak characteristics were determined by powder X-ray diffraction analysis, and a carbon material dispersion composition with high dispersion and conductivity was prepared by combining fluororesin as a dispersant.

Benefits of technology

It achieves high dispersion and conductivity in the solvent, improves the rate characteristics and cycle characteristics of the secondary battery, and is suitable for battery applications with high capacity, high output and high durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119585202A_ABST
    Figure CN119585202A_ABST
Patent Text Reader

Abstract

The present invention can provide a carbon material having high dispersibility and a carbon material dispersion composition. Furthermore, it is possible to provide a composite slurry from which an electrode film having high conductivity can be obtained, and more particularly, it is possible to provide a secondary battery having excellent rate characteristics and cycle characteristics, and a vehicle having a secondary battery. Provided is a carbon material satisfying the following (1) and (2). (1) The BET specific surface area is 400 m2 / g to 650 m2 / g. (2) In powder X-ray diffraction analysis, there are at least two peak values in a diffraction angle 2 [theta] = 24.0-27.0 DEG.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a carbon material and a carbon material dispersion composition. More specifically, it relates to a carbon material dispersion composition comprising a carbon material, a dispersant and a dispersion medium, a composite material slurry comprising the carbon material dispersion composition and an active substance, an electrode film coated with the composite material slurry, a secondary battery comprising an electrode having the electrode film and an electrolyte, and a vehicle comprising the secondary battery. Background Art

[0002] With the popularity of electric vehicles or the miniaturization, lightness and high performance of portable devices, a secondary battery with high energy density is sought, and the capacity of the secondary battery is required to be high. In this context, non-aqueous electrolyte secondary batteries using non-aqueous electrolytes, especially lithium-ion secondary batteries, are used in a large number of devices due to their high energy density and high voltage characteristics.

[0003] As negative electrode materials used in these lithium-ion secondary batteries, carbon materials represented by graphite are used, which have a low potential close to lithium (Li) and a large charge and discharge capacity per unit mass. However, these electrode materials have been used until the charge and discharge capacity per mass is close to the theoretical value, and the energy density per mass of the battery is close to the limit. Therefore, in order to improve the utilization rate of the electrode, discussions have been conducted to reduce the conductive additives or binders that do not contribute to the discharge capacity.

[0004] As conductive additives, carbon materials such as carbon black, Ketjen black, fullerene, graphene, and fine carbon materials are used. In recent years, carbon nanotubes, which are one type of fine carbon materials and have a large specific surface area, are often used. For example, it is known that the electrode film formed by a composite material slurry containing a carbon nanotube dispersion composition and an active material has a low electrode resistance and improves the load resistance or cycle characteristics of the battery (for example, refer to Patent Documents 1 and 2).

[0005] However, conventional carbon nanotubes having a large specific surface area have low wettability in a solvent, and therefore it is difficult to prepare a dispersion composition having a high concentration and excellent dispersion stability.

[0006] Therefore, it is imperative to develop carbon nanotubes that have excellent wettability in a solvent, a high specific surface area, and excellent electrical conductivity.

[0007] As a method for improving the properties of carbon nanotubes, for example, the following method has been proposed: heat-treating carbon nanotubes at 1000° C. to 3000° C. in an inert environment (see Patent Documents 1 and 3). However, the main purpose of these methods is to remove metals and metal oxides contained in the obtained carbon nanotubes, and no detailed research has been conducted on the heat treatment of carbon nanotubes with a large specific surface area, and it is impossible to achieve both dispersibility and conductivity.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent No. 6586197

[0011] Patent Document 2: Japanese Patent Application Publication No. 2011-70908

[0012] Patent Document 3: Japanese Patent No. 6590034 Summary of the invention

[0013] Problems to be solved by the invention

[0014] Therefore, the problem to be solved by the present invention is to provide a carbon material with high dispersibility and conductivity, and a carbon material dispersion composition. In addition, a composite material slurry that can obtain an electrode film with high conductivity is provided. More specifically, a secondary battery with excellent rate characteristics and cycle characteristics is provided, and a vehicle with high safety and improved fuel consumption rate by having the secondary battery is provided.

[0015] Technical means of solving problems

[0016] The inventors of the present invention have made great efforts to solve the above problems. The inventors have found that the Brunauer-Emmett-Teller (BET) specific surface area of ​​carbon materials containing multi-walled carbon nanotubes is 400 m 2 / g~650m 2 / g, and further in the powder X-ray diffraction analysis, there are at least two peaks in the diffraction angle 2θ = 24.0° to 27.0°, thus having high dispersibility. In addition, it is found that by using this carbon material, an electrode film with excellent conductivity can be obtained, and a secondary battery with excellent rate characteristics and cycle characteristics can be obtained. Based on this insight, the inventors and others completed the present invention.

[0017] That is, the present invention includes the following embodiments. The embodiments of the present invention are not limited to the following. [1] A carbon material comprising multiwalled carbon nanotubes and satisfying the following (1) and (2).

[0018] (1) BET specific surface area is 400m 2 / g~650m 2 / g.

[0019] (2) In powder X-ray diffraction analysis, it has at least two peaks within the range of diffraction angle 2θ = 24.0° to 27.0°.

[0020] [2] The carbon material according to [1], wherein when the peak intensity on the low-angle side within the range of diffraction angle 2θ = 24.0° to 27.0° in powder X-ray diffraction analysis is set as A and the peak intensity on the high-angle side is set as B, the B / A ratio is 1.0 to 2.5.

[0021] [3] The carbon material according to [1] or [2], wherein the purity is 99.9% by mass or more.

[0022] [4] The carbon material according to any one of [1] to [3], wherein when the 1560 cm -1 ~1600cm -1 The maximum peak intensity in the range of 1310 cm is set as G, and the peak intensity at 1310 cm is set as -1 ~1350cm -1 When the maximum peak intensity in the range of is set to D, the G / D ratio is 1.0 to 4.5.

[0023] [5] A carbon material dispersion composition comprising the carbon material according to any one of [1] to [4], a dispersant and a dispersion medium.

[0024] [6] The carbon material dispersion composition according to [5], wherein after the carbon material dispersion composition is produced, the viscosity of the carbon material dispersion composition after being stored at 60°C for one week is measured using a B-type viscometer at 25°C and a rotor rotation speed of 6 rpm, and the viscosity is 500 mPa·s to 20,000 mPa·s.

[0025] [7] The carbon material dispersion composition according to any one of [5] to [6], comprising a fluororesin.

[0026] [8] A composite material slurry comprising the carbon material dispersion composition according to any one of [5] to [7] and an active substance.

[0027] [9] An electrode membrane formed from the composite material slurry according to [8].

[0028]

[10] A secondary battery comprising an electrode having the electrode film according to [9] and an electrolyte.

[0029]

[11] A vehicle comprising the secondary battery according to

[10] .

[0030]

[12] A method for producing a carbon material dispersion composition, comprising the steps of: mixing a carbon material dispersion composition (I) comprising a carbon material, a dispersant, and a dispersion medium, and a carbon material dispersion composition (II) comprising single-walled carbon nanotubes and a fluororesin (except for the carbon material dispersion composition (I));

[0031] The carbon material is a carbon material including multi-walled carbon nanotubes and satisfying the following (1) and (2).

[0032] (1) BET specific surface area is 400m 2 / g~650m 2 / g.

[0033] (2) In powder X-ray diffraction analysis, it has at least two peaks within the range of diffraction angle 2θ = 24.0° to 27.0°.

[0034] Effects of the Invention

[0035] The carbon material containing multi-layered carbon nanotubes of the present invention has excellent dispersibility. By using such a carbon material, a carbon material dispersion composition, a composite material slurry, and an electrode film having excellent conductivity can be obtained. In addition, a secondary battery having excellent rate characteristics and cycle characteristics can be obtained. Thus, even a hybrid vehicle, a plug-in hybrid vehicle, an electric vehicle, and other vehicle uses that require high capacity, high output, and high durability of the secondary battery carried can be preferably used. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] [ Figure 1 ] Figure 1 This is an X-ray diffraction (XRD) spectrum of the carbon material used in the examples or comparative examples of the present invention. It can be confirmed that the carbon material of the example has two peaks in the range of diffraction angle 2θ = 24.0° to 27.0°. DETAILED DESCRIPTION

[0037] Hereinafter, the carbon material, carbon material dispersion composition, composite material slurry, electrode film, and secondary battery of the present invention are described in detail, but are not limited thereto. In addition, the numerical values ​​determined in this specification are values ​​obtained by the methods disclosed in the embodiments or examples. In this specification, carbon nanotubes are sometimes described as "CNTs".

[0038] In addition, the numerical range specified by "to" in this specification includes the numerical values ​​before and after "to" as the range of the lower limit and the upper limit. In addition, various components appearing in this specification can be used independently alone or in combination of two or more unless otherwise noted.

[0039] Carbon Materials

[0040] The carbon material of the present embodiment includes multiwalled carbon nanotubes and satisfies the following (1) and (2).

[0041] (1) BET specific surface area is 400m 2 / g~650m 2 / g.

[0042] (2) In powder X-ray diffraction analysis, it has at least two peaks within the range of diffraction angle 2θ = 24.0° to 27.0°.

[0043] A carbon nanotube is a structure formed by winding a flat graphite into a cylindrical shape. A single-layer carbon nanotube has a structure formed by winding a single layer of graphite, and a multi-layer carbon nanotube has a structure formed by winding two or more layers of graphite. In addition, the side wall of the carbon nanotube may not be a graphite structure. For example, a carbon nanotube having a side wall having an amorphous structure may also be used as the carbon nanotube.

[0044] The carbon material of the present embodiment preferably contains multi-walled carbon nanotubes as a main component, but may contain single-walled carbon nanotubes as a mixture.

[0045] The main component refers to a component having the highest content among the components constituting the carbon material.

[0046] As the content rate of multilayer carbon nanotubes contained in the carbon material of the present embodiment, specifically, in 100 mass % of the carbon material, it is preferably 50 mass % or more and 99.9 mass % or less, and further preferably 60 mass % or more and 98 mass % or less. The content of multilayer carbon nanotubes can be obtained, for example, by using thermogravimetry-differential thermal analysis (TG-DTA), after heating to 25°C to 600°C in a nitrogen environment, reducing the heating temperature to 400°C, switching the atmosphere from nitrogen to air, and heating to 400°C to 1000°C. At this time, the weight loss when heated to 600°C in a nitrogen environment can be considered as the weight of amorphous carbon, the weight loss when heated to 800°C after switching to an air environment can be considered as the weight of multilayer carbon nanotubes, and the weight loss when heated to 800°C to 1000°C can be considered as the weight of crystalline carbon.

[0047] By including the multi-walled carbon nanotubes, when used as a conductive material of a secondary battery, the load resistance or cycle characteristics of the secondary battery can be improved.

[0048] The BET specific surface area of ​​the carbon material of this embodiment is 400 m 2 / g~650m 2 / g, preferably 450m 2 / g~600m 2 / g, and more preferably 450m 2 / g~550m 2 / g.

[0049] Based on (2), the BET specific surface area is 400 m2 of (1). 2 / g~650m 2 / g range, thereby, a small amount and efficient conductive network can be formed, and the amount of conductive material in the electrode can be reduced. As a result, the degree of freedom of battery design such as adding active materials or binder resins becomes higher. Furthermore, when making composite material slurry, the composite of active materials and carbon nanotubes becomes easier to advance, so it is easy to obtain an electrode film with a homogeneous conductive network coated with carbon nanotubes on the surface of the active material, which can inhibit the decomposition reaction of the electrolyte at the interface between the electrolyte and the active material, and improve the cycle characteristics of the battery. For example, the BET specific surface area of ​​the carbon material of this embodiment can be 400m 2 / g~650m 2 / g, 420m 2 / g~620m 2 / g, 450m 2 / g~600m 2 / g、500m 2 / g~570m 2 / g, or 520m 2 / g~550m 2 / g.

[0050] The BET specific surface area can be measured by the BET method described in Japanese Industrial Standards (JIS) Z8833.

[0051] The carbon material of the present embodiment has at least two peaks in the range of diffraction angle 2θ=24.0° to 27.0° in powder X-ray diffraction analysis. The case of having two peaks is preferred.

[0052] It is speculated that the peak value of the low angle side in the two peak values ​​is derived from the multilayer carbon nanotube, and the peak value in the high angle side is mainly derived from the peak value of graphite. By being a carbon material with such a peak value, dispersibility and electrical conductivity can be excellent. It is believed that the reason for excellent dispersibility is that the amorphous carbon component present in the defective portion of the multilayer carbon nanotube is selectively graphitized, so it is easy to obtain multilayer carbon nanotubes with consistent shapes when making a dispersed composition. In addition, it is believed that the reason for excellent electrical conductivity is that the defective portion of the multilayer carbon nanotube is graphitized, and crystallinity improves, and the electrical conductivity of the multilayer carbon nanotubes as the main component of the carbon material is improved, and the contact resistance of the multilayer carbon nanotubes is reduced.

[0053] The B / A ratio, where the peak intensity on the low angle side is A and the peak intensity on the high angle side is B, is preferably 1.0 to 2.5, more preferably less than 1.5. Such a carbon material provides better dispersibility and conductivity.

[0054] Furthermore, when there are two or more peaks, it is preferable that the above-mentioned necessary conditions are satisfied for two peaks having larger peak intensities.

[0055] The carbon material of this embodiment preferably has a lattice plane spacing d002 calculated by powder X-ray diffraction analysis of

[0056] For powder X-ray diffraction analysis, the carbon material and high-purity silicon are thoroughly mixed in an agate mortar, and then packed into a predetermined sample holder in a manner that the surface is flat, and then placed in a powder X-ray diffraction analysis device, and the irradiation angle of the X-ray source is changed from 5° to 80° for measurement. As the X-ray source, for example, CuKα rays can be used.

[0057] The sulfur content of the carbon material of the present embodiment is preferably 500 ppm or less, and more preferably 100 ppm or less. A sulfur content of the above content or less is preferred because a decrease in dispersibility can be suppressed.

[0058] The purity of the carbon material of the present embodiment is preferably 95% by mass or more, more preferably 99% by mass or more, and further preferably 99.9% by mass or more. In the case where the purity of the carbon material is higher than that described, there are few conductive foreign matters other than the carbon material, so the storage stability of the secondary battery can be further improved. For example, with respect to the B / A ratio, the purity of the carbon material of the present embodiment may be 95.00% by mass or more, 99.00% by mass or more, 99.90% by mass or more, or 99.99% by mass or more. The carbon purity of carbon nanotubes can be measured by an inductively coupled plasma (ICP) emission spectrophotometer, and specifically can be obtained by the method described in the examples.

[0059] The purity of the carbon material can be obtained by subtracting the total weight of iron, cobalt, magnesium, aluminum, copper, nickel, zirconium oxide, and molybdenum contained in the carbon material from the weight of the carbon material. The total content of iron, cobalt, magnesium, aluminum, copper, nickel, zirconium oxide, and molybdenum is preferably 300 ppm or less, more preferably 100 ppm or less.

[0060] Regarding the content of the above-mentioned metals and sulfur, after drying the carbon material, acid decomposition can be carried out using a microwave sample pretreatment device (manufactured by Milestone-general, ETHOS 1) to extract the metals contained in the carbon material, and then analysis can be carried out using a composite ICP emission spectrometer (manufactured by Agilent, 720-ES).

[0061] Regarding the G / D ratio (peak ratio of the G-band to the D-band) of the carbon material of the present embodiment, when the peaks at 1560 cm -1 ~1600cm -1The maximum peak intensity in the range of 1310 cm is set as G, and the peak intensity at 1310 cm is set as -1 ~1350cm -1 When the maximum peak intensity in the range of is defined as D, the G / D ratio is preferably 1.0 to 5.0, and more preferably 1.0 to 4.5. The G / D ratio can be measured using a Raman microscope according to the procedure of the examples.

[0062] It is believed that when the G / D ratio of the carbon material is within the above range, the defects of the multilayer carbon nanotubes are graphitized, the contact resistance between the multilayer carbon nanotubes becomes small, and good conductivity is easily obtained. In addition, it is speculated that the reason is that the amount of functional groups on the surface of the multilayer carbon nanotubes is appropriate, the affinity with the solvent is good, and the dispersibility becomes better.

[0063] The average outer diameter of the carbon material of the present embodiment is preferably 4nm to 25nm, more preferably 4nm to 9nm. When the average outer diameter is within the range, it is easy to form a good conductive network in the electrode, and the active material inside the secondary battery is evenly utilized during charging and discharging, so the degradation of the active material is suppressed, and the cycle characteristics of the secondary battery are further improved. For example, the average outer diameter of the carbon material of the present embodiment may be 4nm to 25nm, 4.5nm to 20nm, 5nm to 15nm, 5.5nm to 10nm, or 6nm to 7nm.

[0064] The outer diameter and average outer diameter of the carbon material of the present embodiment are obtained as follows. First, the carbon material is observed and photographed using a transmission electron microscope. Next, 300 random carbon materials are selected from the observed photographs and their outer diameters are measured. Next, the average outer diameter (nm) of the carbon material is calculated as the average value of the outer diameter.

[0065] The volume resistivity of the carbon material of this embodiment is preferably 1.0×10 -2 Ω·cm~3.0×10 -2 Ω·cm, more preferably 1.0×10 -2 Ω·cm~2.0×10 -2 Ω·cm.

[0066] The volume resistivity of the carbon material can be measured using a powder resistivity measuring device (Mitsubishi Chemical Analytech Co., Ltd.: Loresta GP Powder Resistivity Measuring System MCP-PD-51). When the volume resistivity of the carbon material is within the above range, the conductivity of the electrode film tends to be good, and a secondary battery with excellent rate characteristics and cycle characteristics is easily obtained.

[0067] The ash content of the carbon material of the present embodiment is preferably 500 ppm or less, and more preferably 300 ppm or less.

[0068] <Method for producing carbon material>

[0069] The carbon material of this embodiment may be a carbon material produced by any method as long as it contains multi-walled carbon nanotubes and satisfies the characteristics of (1) and (2). Carbon materials can generally be produced by laser ablation, arc discharge, thermal chemical vapor deposition (CVD), plasma CVD, and combustion, but are not limited to these. For example, the carbon material can also be produced by contacting a carbon source with a catalyst at 500°C to 1000°C in an environment with an oxygen concentration of less than 1% by volume. The carbon source may be at least one of a hydrocarbon and an alcohol.

[0070] The carbon material of this embodiment is more preferably prepared by further heat-treating the carbon material, wherein the carbon material is -1 ~1600cm -1 The maximum peak intensity in the range of 1310 cm is set as G, and the peak intensity at 1310 cm is set as -1 ~1350cm -1 The carbon material has a G / D ratio of less than 1.0 when the maximum peak intensity in the range of is defined as D. The temperature of the heat treatment is preferably 1000°C to 2000°C, more preferably 1400°C to 1800°C, and even more preferably 1400°C to 1600°C.

[0071] The carbon material of this embodiment is preferably prepared by further heat-treating a carbon material containing iron, cobalt and / or nickel, and more preferably prepared by further heat-treating a carbon nanotube containing 1000ppm to 10000ppm of iron and / or cobalt. Iron, cobalt and nickel have the effect of promoting graphitization, and by optimizing the amount of iron, cobalt and nickel contained in the carbon nanotube, graphitization can be performed at low temperature. Therefore, it is believed that the defective parts of the carbon nanotube can be selectively graphitized, and the conductivity can be improved without losing the characteristics of the carbon nanotube itself.

[0072] 《Carbon material dispersion composition》

[0073] The carbon material dispersion composition contains at least the carbon material of the present invention, a dispersant, and a dispersion medium.

[0074] In addition, the carbon material dispersion composition preferably contains a fluororesin. By containing the fluororesin in the carbon material dispersion composition, the carbon material is less likely to aggregate due to the steric hindrance caused by the fluororesin, and a carbon material dispersion composition with a good dispersion state is easily obtained.

[0075] When a fluororesin is used as a dispersant, compatibility with a binder resin in preparing a composite material slurry described later is excellent. Also, when a fluororesin is used as a binder resin, it is preferred from the viewpoint of electrochemical oxidation-reduction resistance.

[0076] In addition, in this specification, when an active material is included, it is defined as a composite material slurry.

[0077] <Dispersant>

[0078] The dispersant of the present embodiment is not particularly limited within the range that can stabilize the dispersion of the carbon material, and surfactants, resin-type dispersants, fluororesins, etc. can be used. Surfactants are mainly classified into anionic, cationic, nonionic and amphoteric. According to the characteristics required for the dispersion of the carbon material, a preferred type of dispersant can be used in a preferred amount.

[0079] The content of the dispersant is preferably 1 to 100 parts by mass, more preferably 10 to 100 parts by mass, and further preferably 20 to 50 parts by mass, relative to 100 parts by mass of the carbon material. When the amount of the dispersant is within the above range, the amount of the dispersant adsorbed on the surface of the carbon material is appropriate, and a carbon material dispersion composition having excellent conductivity and dispersion stability is easily obtained.

[0080] When anionic surfactants are selected, their types are not particularly limited. Specifically, fatty acid salts, polysulfonates, polycarboxylates, alkyl sulfate ester salts, alkyl aryl sulfonates, alkyl naphthalene sulfonates, dialkyl sulfonates, dialkyl sulfosuccinates, alkyl phosphates, polyoxyethylene alkyl ether sulfates, polyoxyethylene alkyl aryl ether sulfates, naphthalenesulfonic acid formalin condensates, polyoxyethylene alkyl phosphoric acid sulfonates, glyceryl borate fatty acid esters and polyoxyethylene glycerol fatty acid esters can be listed, but they are not limited to these. Furthermore, specifically, sodium dodecylbenzene sulfonate, sodium laurate sulfate, sodium polyoxyethylene lauryl ether sulfate, polyoxyethylene nonylphenyl ether sulfate salts and sodium salts of β-naphthalenesulfonic acid formalin condensates can be listed, but they are not limited to these.

[0081] In addition, as cationic surfactants, there are alkylamine salts and quaternary ammonium salts. Specifically, stearylamine acetate, trimethyl coconut oil ammonium chloride, trimethyl tallow ammonium chloride, dimethyl dioleyl ammonium chloride, methyl oleyl diethanol chloride, tetramethyl ammonium chloride, lauryl pyridinium chloride, lauryl pyridinium bromide, lauryl pyridinium disulfate, cetyl pyridinium bromide, 4-alkyl mercaptopyridine, poly (vinyl pyridine) - dodecyl bromide and dodecyl benzyl triethyl ammonium chloride can be listed, but it is not limited to these. In addition, as amphoteric surfactants, aminocarboxylates can be listed, but it is not limited to these.

[0082] In addition, as nonionic surfactants, polyoxyethylene alkyl ethers, polyoxyalkylene derivatives, polyoxyethylene phenyl ethers, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters and alkyl allyl ethers can be listed, but they are not limited to these. Specifically, polyoxyethylene lauryl ether, sorbitan fatty acid esters and polyoxyethylene octyl phenyl ether can be listed, but they are not limited to these.

[0083] The selected surfactant is not limited to a single surfactant. Therefore, two or more surfactants can be used in combination. For example, a combination of anionic surfactant and nonionic surfactant, or a combination of cationic surfactant and nonionic surfactant can be used. The blending amount at this time is preferably set to a preferred blending amount relative to each surfactant component. As a combination, a combination of anionic surfactant and nonionic surfactant is preferred. The anionic surfactant is preferably a polycarboxylate. The nonionic surfactant is preferably polyoxyethylene phenyl ether.

[0084] In addition, as the resin type dispersant, specifically, cellulose derivatives (cellulose acetate, cellulose acetate butyrate, cellulose butyrate, cyanoethyl cellulose, ethyl hydroxyethyl cellulose, nitrocellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, etc.), polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, hydrogenated nitrile rubber, polyacrylonitrile polymers, etc. are listed. Methyl cellulose, ethyl cellulose, carboxymethyl cellulose, polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, hydrogenated nitrile rubber, polyacrylonitrile polymers are particularly preferred, and polyvinyl pyrrolidone, polyvinyl butyral, hydrogenated nitrile rubber is further preferred. The molecular weight of the resin type dispersant is preferably 10,000 to 300,000, and more preferably 10,000 to 150,000.

[0085] Fluororesin is a polymer compound having fluorine atoms in the molecule, and specific examples thereof include polyvinylidene fluoride, polyvinyl fluoride, and tetrafluoroethylene.

[0086] When a fluororesin is used as a dispersant, it is more preferably used together with a dispersant other than a fluororesin such as a surfactant or a resin-type dispersant. When a surfactant or a resin-type dispersant and a fluororesin are used as a dispersant, the surfactant or the resin-type dispersant is easily adsorbed on the surface of the carbon material, and the wettability or dispersibility is easily improved.

[0087] The weight average molecular weight of the fluororesin of the present embodiment is preferably 10,000 to 2,000,000, more preferably 100,000 to 1,000,000, and particularly preferably 200,000 to 1,000,000.

[0088] The content of the fluororesin in this embodiment is preferably 1 to 100 parts by mass, and more preferably 10 to 70 parts by mass, based on 100 parts by mass of the carbon material in the carbon material dispersion composition. When the content of the fluororesin is within the above range, a carbon material dispersion composition with good fluidity can be easily obtained.

[0089] In addition, in addition to the dispersant, it is preferred to add an amine compound or an inorganic base. As the amine compound, a first amine (primary amine), a second amine (secondary amine), and a third amine (tertiary amine) are used, and ammonia or quaternary ammonium compounds are not included. In addition to monoamines, amine compounds such as diamines, triamines, and tetramines having multiple amino groups in the molecule can also be used. Specifically, for example, aliphatic primary amines such as methylamine, ethylamine, butylamine, and octylamine, aliphatic secondary amines such as dimethylamine, diethylamine, and dibutylamine, aliphatic tertiary amines such as trimethylamine, triethylamine, and dimethyloctylamine, alanine, methionine, proline, serine, asparagine, glutamine, lysine, arginine, histidine, aspartic acid, glutamic acid, cysteine, dimethylaminoethanol, monoethanolamine, diethanolamine, methylethanolamine, triethanolamine, alkanolamines such as triethanolamine, hexamethylenetetramine, morpholine, piperidine, etc. can be listed, but it is not limited to these. Examples of the inorganic base include alkali metal hydroxides, alkaline earth metal hydroxides, alkali metal carbonates, alkaline earth metal carbonates, alkali metal phosphates, alkaline earth metal phosphates, and the like.

[0090] The amount of the amine compound and the inorganic base used is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, relative to 100 parts by mass of the dispersant. The amount of the amine compound and the inorganic base used is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, and further preferably 5 parts by mass or less, relative to 100 parts by mass of the dispersant.

[0091] <Dispersion medium>

[0092] As long as the carbon material can be dispersed, the solvent used as the dispersion medium of the present embodiment is not limited, and water or an amide-based organic solvent is preferred. As amide-based organic solvents, there can be cited: N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methylcaprolactam, etc. In particular, it is more preferred to include at least one selected from the group consisting of N-methyl-2-pyrrolidone and N-ethyl-2-pyrrolidone.

[0093] When an amide-based organic solvent is used as the dispersion medium, the water content is preferably 1000 ppm or less, and more preferably 500 ppm or less.

[0094] The content of the dispersion medium of the present embodiment is based on the carbon material dispersion composition (100 mass %), preferably 90 mass % to 99 mass %, and more preferably 95 mass % to 99 mass %. In the case of the above range, it is easy to obtain a carbon material dispersion composition with fluidity, and it is easy to obtain a carbon material dispersion composition with excellent dispersion stability. By using a carbon material composition with excellent dispersion stability, an electrode film with stable conductivity can be obtained, and the quality of the secondary battery is easy to stabilize.

[0095] <Binder resin>

[0096] The carbon material dispersion composition of the present embodiment may contain a binder resin.

[0097] The binder resin is a resin for binding carbon material substances together.

[0098] There are no particular restrictions on the binder resin, and examples thereof include: polymers or copolymers containing fluororesins, ethylene, propylene, vinyl chloride, vinyl acetate, vinyl alcohol, maleic acid, acrylic acid, acrylates, methacrylic acid, methacrylates, acrylonitrile, styrene, vinyl butyral, vinyl acetal, vinyl pyrrolidone, etc. as structural units; polyurethane resins, polyester resins, phenol resins, epoxy resins, phenoxy resins, urea resins, melamine resins, alkyd resins, acrylic resins, formaldehyde resins, silicone resins, fluororesins; cellulose resins such as carboxymethyl cellulose; rubbers such as styrene butadiene rubber; conductive resins such as polyaniline and polyacetylene, etc.

[0099] Among them, from the viewpoint of electrochemical redox resistance, it is preferred to use a fluororesin as the binder resin.

[0100] As the fluororesin, the same fluororesin as described in the dispersant can be used.

[0101] As the fluororesin of the present embodiment, for example, polyvinylidene fluoride, polyvinyl fluoride, or tetrafluoroethylene is preferable.

[0102] The weight average molecular weight of the fluororesin of the present embodiment is preferably 10,000 to 2,000,000, more preferably 100,000 to 1,000,000, and particularly preferably 200,000 to 1,000,000.

[0103] The content of the binder resin in this embodiment is preferably 1 to 100 parts by mass, preferably 10 to 70 parts by mass, based on 100 parts by mass of the carbon material in the carbon material dispersion composition. When the content of the binder resin is within the above range, a carbon material dispersion composition with good fluidity can be easily obtained.

[0104] <Method for producing carbon material dispersion composition>

[0105] In order to obtain the carbon material dispersion composition of the present embodiment, it is preferable to perform a process of dispersing the carbon material in a dispersion medium. The dispersing device used for performing the process is not particularly limited.

[0106] In addition, preferably, after the carbon material and the dispersant are dispersed in the dispersion medium, a binder resin is mixed in the obtained dispersion composition and used after homogenization. As a mixing method, various methods known in the past can be carried out. As a binder resin, a fluororesin is preferably used.

[0107] The carbon material dispersion composition of the present embodiment may contain single-walled carbon nanotubes other than the carbon material of the present invention in addition to the carbon material of the present invention.

[0108] In this case, the carbon material dispersion composition can be prepared by various conventionally known methods.

[0109] Specifically, a mixed solution containing the carbon material of the present invention, single-walled carbon nanotubes, a dispersant, a dispersion medium, and any components as required may be dispersed to prepare a carbon material dispersion composition and used. Alternatively, a carbon material dispersion composition (I) containing the carbon material of the present invention and a carbon material dispersion composition (II) containing single-walled carbon nanotubes (except for the case of the carbon material dispersion composition (I)) may be separately prepared and used.

[0110] Among them, from the viewpoint of stability and battery characteristics, it is preferred that the carbon material dispersion composition (I) contains a carbon material, a dispersant, and a dispersion medium, and the carbon material dispersion composition (II) contains single-walled carbon nanotubes and a fluororesin.

[0111] The order of mixing the carbon material of the present invention, the single-walled carbon nanotubes, the dispersant, and the dispersion medium is not particularly limited, and each may be added sequentially, or any two or more may be added simultaneously.

[0112] Among them, from the viewpoint of inhibiting the agglomeration of carbon materials and the gelation of fluororesins, preferred is the manufacturing method (I): a method comprising the following step (I-1), or the manufacturing method (II): a method comprising the following steps (II-1) to (II-3), and more preferred is the manufacturing method (II): a method comprising the following steps (II-1) to (II-3).

[0113] Manufacturing method (I)

[0114] (I-1) A step of dispersing a mixed solution containing the carbon material of the present invention, single-walled carbon nanotubes, a fluororesin, and a dispersion medium.

[0115] ·Manufacturing method (II)

[0116] (II-1) A step of dispersing a mixed solution containing the carbon material of the present invention, a dispersant, and a dispersion medium to produce a carbon material dispersion composition (I).

[0117] (II-2) A step of dispersing a mixed solution containing single-walled carbon nanotubes, a fluororesin, and a dispersion medium to produce a carbon material dispersion composition (II).

[0118] (II-3) A step of mixing the carbon material dispersion composition (I) and the carbon material dispersion composition (II).

[0119] As the dispersing device, a dispersing machine commonly used in pigment dispersion, etc. can be used. For example, mixers such as dispersers, homomixers, and planetary mixers, homogenizers (Advanced Digital Sonifer (registered trademark), model (MODEL) 450DA manufactured by BRANSON, "clearmix" manufactured by M-technique, "filmix" manufactured by PRIMIX, "abramix" manufactured by Silverson, etc.), paint conditioners (manufactured by Red Devil), colloid mills ("PUC colloid mill" manufactured by PUC, "colloid mill MK" manufactured by IKA), cone mills ("cone mill MKO" manufactured by IKA, etc.), ball mills, sand mills (SHINMARU The present invention also includes media dispersers such as "Dyno-mill" manufactured by ENTERPRISES, etc.), attritors, pearl mills (such as "DCP mill" manufactured by Eirich), co-ball mills, high-pressure homogenizers (such as "Jenius PY" manufactured by Jenius, "Star burst" manufactured by SUGINO Machine, "nanomizer" manufactured by Nanomizer, etc.), media-free dispersers such as "clear SS-5" manufactured by M-technique, "MICROS" manufactured by Nara Machinery, and other roll mills, but are not limited to these.

[0120] The carbon material dispersion composition of this embodiment preferably has a moisture content of 100 ppm to 1500 ppm, more preferably 200 ppm to 1000 ppm. When the moisture content of the carbon material dispersion composition is within the above range, gelation of the composite slurry described below is suppressed, and composite slurry and electrode film of stable quality are easily obtained.

[0121] The amount of the dispersant in the carbon material dispersion composition of the present embodiment is preferably 10 to 100 parts by mass, more preferably 20 to 50 parts by mass, relative to 100 parts by mass of the carbon material. When the amount of the dispersant in the carbon material dispersion composition is within the above range, the amount of the dispersant adsorbed on the surface of the carbon material is appropriate, and a carbon material dispersion composition having excellent conductivity and dispersion stability is easily obtained.

[0122] The content of the carbon material in the carbon material dispersion composition of the present embodiment is preferably 0.5% to 5.0% by mass, more preferably 1.0% to 3.5% by mass, and further preferably 1.5% to 3.0% by mass, based on 100% by mass of the carbon material dispersion composition. When the amount of the carbon material in the carbon material dispersion composition is within the above range, when the carbon material dispersion composition is prepared, the multiwalled carbon nanotubes are appropriately dispersed, and a carbon material dispersion composition having excellent electrical conductivity and dispersion stability is easily obtained.

[0123] The initial viscosity of the carbon material dispersion composition of the present embodiment measured at 6 rpm using a Brookfield viscometer is preferably 100 mPa·s or more and less than 10,000 mPa·s, more preferably 500 mPa·s or more and less than 5,000 mPa·s.

[0124] It is considered that when the initial viscosity of the carbon material dispersion composition is within the above range, the dispersion state of the multiwalled carbon nanotubes contained in the carbon material composition is appropriate and a conductive network is easily formed.

[0125] The liquid properties of the carbon material dispersion composition can be judged by evaluating the thixotropy (thixotropic index (TI) value) of the carbon material composition in the following manner. After the carbon material composition is allowed to stand in a thermostatic bath at 25°C for 24 hours, the viscosity is measured at a B-type viscometer rotor rotation speed of 6 rpm, and then the viscosity is measured at 60 rpm. At this time, when the viscosity measured at 6 rpm is set to S and the viscosity measured at 60 rpm is set to T, the S / T ratio becomes the TI value. The TI value of the carbon material composition is preferably greater than 2 and less than 7, and more preferably greater than 3 and less than 5. When the TI value is within the range, the aspect ratio of the multilayered carbon nanotubes contained in the carbon material composition is appropriate, and it is easy to obtain a carbon material composition with excellent conductivity and stability over time.

[0126] Regarding the carbon material dispersion composition of this embodiment, the viscosity after the dispersion composition is manufactured and stored at 60°C for one week, and the viscosity measured by a B-type viscometer at 25°C and a rotor rotation speed of 6 rpm after cooling to 25°C is preferably 500 mPa·s to 20,000 mPa·s, and more preferably 2,000 mPa·s to 10,000 mPa·s.

[0127] It is believed that the composition ratio of the carbon material, dispersant, and dispersion medium of the carbon material dispersion composition having a viscosity within the above range or the dispersion process is appropriate, and the dispersion stability is good. The adsorption reaction of the dispersant contained in the carbon material dispersion composition on the surface of the carbon material is an endothermic reaction, so by evaluating the viscosity of the carbon material dispersion composition after storage under high temperature conditions, it is possible to determine the sufficient amount of dispersant required to obtain a carbon material dispersion composition with excellent dispersion stability.

[0128] Composite material slurry

[0129] The composite material slurry of the present embodiment contains a carbon material dispersion composition and an active material, that is, preferably contains at least the carbon material of the present invention, a dispersant, a dispersion medium, and an active material, and contains a fluororesin as a dispersant or a binder resin.

[0130] <Active substances>

[0131] The active material of this embodiment is a material that serves as a basis for the battery reaction. In terms of electromotive force, the active material is divided into a positive electrode active material and a negative electrode active material.

[0132] In this specification, the positive electrode active material and the negative electrode active material are sometimes simply referred to as "active material". The so-called active material is a material that serves as a basis for battery reaction. In terms of electromotive force, active materials are divided into positive electrode active materials and negative electrode active materials.

[0133] There are no particular limitations on the positive electrode active material, and metal compounds such as metal oxides and metal sulfides that can be doped or embedded with lithium ions, and conductive polymers can be used. Examples include oxides of transition metals such as Fe, Co, Ni, and Mn, composite oxides with lithium, inorganic compounds such as transition metal sulfides, and the like. Specifically, MnO, V 2 O 5 、V 6 O 13 、TiO 2 Transition metal oxide powders, composite oxide powders of lithium and transition metals such as lithium nickel oxide, lithium cobalt oxide, lithium manganate, and lithium manganate with a spinel structure, lithium iron phosphate-based materials as olivine-structured phosphate compounds, TiS 2 , FeS and other transition metal sulfide powders. In addition, conductive polymers such as polyaniline, polyacetylene, polypyrrole, polythiophene, etc. can also be used. In addition, the above inorganic compounds or organic compounds can also be mixed and used.

[0134] The negative electrode active material is not particularly limited as long as it can be doped or embedded with lithium ions. For example, metal Li, alloys thereof such as tin alloys, silicon alloys, lead alloys, LixFe 2O 3 、LixFe 3 O 4 、LixWO 2 (x is a number where 0<x<1), metal oxides such as lithium titanate, lithium vanadate, lithium silicate, conductive polymers such as polyacetylene, polyparaphenylene, amorphous carbonaceous materials such as soft carbon or hard carbon, artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, carbon black, mesophase carbon black, resin calcined carbon materials, gas-grown carbon fibers, carbon fibers, etc. These negative electrode active materials can also be used alone or in combination.

[0135] The positive electrode active material is preferably a composite oxide containing transition metals such as Al, Fe, Co, Ni, and Mn and lithium, more preferably a composite oxide containing any one of Al, Co, Ni, and Mn and lithium, and particularly preferably a composite oxide containing Ni and / or Mn and lithium. When using these active materials, particularly good effects can be obtained.

[0136] The BET specific surface area of ​​the active material is preferably 0.1 m 2 / g~10m 2 / g, more preferably 0.2m 2 / g~5m 2 / g, and more preferably 0.3m 2 / g~3m 2 / g.

[0137] The average particle size of the active material is preferably in the range of 0.05 μm to 100 μm, and more preferably in the range of 0.1 μm to 50 μm. The average particle size of the active material referred to in this specification is the average value of the particle size of the active material measured using an electron microscope.

[0138] <Method for producing composite material slurry>

[0139] In order to obtain the composite material slurry of the present embodiment, it is preferred to perform a process of adding an active substance to the carbon material dispersion composition and dispersing it. The dispersing device used for performing the process is not particularly limited. Regarding the composite material slurry, the composite material slurry can be obtained using the dispersing device described in the carbon material dispersion composition.

[0140] The content of the active material in the composite material slurry is preferably 20% to 85% by mass, and particularly preferably 40% to 85% by mass, based on 100% by mass of the composite material slurry.

[0141] The content of the carbon material in the composite material slurry is preferably 0.05 to 10% by mass, preferably 0.1 to 5% by mass, and preferably 0.1 to 3% by mass, based on 100% by mass of the active material.

[0142] The content of the fluororesin in the composite material slurry is preferably 0.5 to 20% by mass, more preferably 1 to 10% by mass, and particularly preferably 1 to 5% by mass, based on 100% by mass of the active material.

[0143] The solid content concentration of the composite material slurry is preferably 30% to 90% by mass, more preferably 40% to 85% by mass, based on 100% by mass of the composite material slurry.

[0144] The water content in the composite material slurry is preferably 500 ppm or less, more preferably 300 ppm or less, and particularly preferably 100 ppm or less.

[0145] "electrode"

[0146] The electrode film of this embodiment includes an electrode film formed of a current collector and a composite material slurry. The electrode film is a coating film of the composite material slurry. For example, it is a coating film formed by coating the composite material slurry on the current collector and drying it to form an electrode composite material layer.

[0147] The material or shape of the current collector used in the electrode film of the present embodiment is not particularly limited, and the material and shape suitable for various secondary batteries can be appropriately selected. For example, as the material of the current collector, metals or alloys such as aluminum, copper, nickel, titanium, or stainless steel can be listed. In addition, as the shape, a foil on a flat plate can generally be used, but a current collector with a roughened surface, a perforated foil-shaped current collector, and a mesh-shaped current collector can also be used.

[0148] As a method for coating the composite material slurry on the collector to form an electrode film, there is no particular limitation, and known methods can be used. Specifically, die coating, dip coating, roll coating, blade coating, spray coating, gravure coating, screen printing or electrostatic coating can be listed, and as a drying method, placement drying, air supply drying machine, warm air drying machine, infrared heating machine, far infrared heating machine, etc. can be used, but it is not particularly limited to these.

[0149] In addition, after coating, a rolling treatment using a flat plate press or a calender roll may be performed. The thickness of the electrode composite material layer is generally 1 μm or more and 500 μm or less, and preferably 10 μm or more and 300 μm or less.

[0150] Secondary Batteries

[0151] The secondary battery of the present embodiment includes an electrode having the electrode film of the present invention and an electrolyte.

[0152] The carbon material of the present invention forms a good conductive network in the secondary battery electrode, so the rate characteristics are excellent, and the active material is used homogeneously during charging and discharging, so the degradation of the active material is not easy to aggravate. Furthermore, overcharging and overdischarging during charging and discharging are suppressed. Therefore, it is not easy to cause the degradation of battery characteristics caused by electrolyte decomposition or metal precipitation, and the cycle characteristics are excellent.

[0153] As the positive electrode, a composite material slurry containing a positive electrode active material is applied to a current collector and then dried to form an electrode film.

[0154] As the negative electrode, a composite material slurry containing a negative electrode active material is applied to a current collector and then dried to form an electrode film.

[0155] As the electrolyte, various conventionally known electrolytes that allow ions to move can be used. For example, LiBF 4 、LiClO 4 、LiPF 6 、LiAsF 6 、LiSbF 6 、LiCF 3 SO 3 、Li(CF 3 SO 2 ) 2 N, LiC 4 F 9 SO 3 、Li(CF 3 SO 2 ) 3 C, LiI, LiBr, LiCl, LiAlCl, LiHF 2 , LiSCN, or LiBPh 4 (wherein Ph is phenyl) etc., but it is not limited to these, and an electrolyte containing a sodium salt may also be used. The electrolyte is preferably dissolved in a non-aqueous solvent and used as an electrolytic solution.

[0156] The non-aqueous solvent is not particularly limited, and examples thereof include carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; lactones such as γ-butyrolactone, γ-valerolactone, and γ-octalactone; glyme such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-methoxyethane, 1,2-ethoxyethane, and 1,2-dibutoxyethane; esters such as methyl formate, methyl acetate, and methyl propionate; sulfoxides such as dimethyl sulfoxide and cyclopentane; and nitriles such as acetonitrile. These solvents may be used alone or in combination of two or more.

[0157] The secondary battery of the present embodiment preferably includes a separator. Examples of the separator include polyethylene nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, and nonwoven fabrics subjected to a hydrophilic treatment, but the separator is not particularly limited to these.

[0158] The structure of the secondary battery of this embodiment is not particularly limited, and generally includes a positive electrode, a negative electrode, and a separator provided as needed, and can be made into various shapes according to the purpose of use, such as paper type, cylindrical type, button type, and stacked type.

[0159] The use of the secondary battery of this embodiment is not particularly limited, and specifically, it can be used for power supply of civilian equipment such as mobile phones, laptop computers, and digital cameras; emergency power supply of hospitals, factories, and buildings; and vehicle use such as hybrid vehicles, plug-in hybrid vehicles, electric vehicles, auxiliary bicycles, and railway vehicles. The secondary battery can, for example, recover regenerative energy of vehicle power.

[0160] Among them, since it is a secondary battery with high charge and discharge performance and excellent cycle characteristics, it can be preferably used in vehicles, and a vehicle with high safety and improved fuel consumption can be obtained. Furthermore, even in the case of vehicle use where charging and discharging at a large current is expected, an excellent effect can be exerted.

[0161] The mounting position of the secondary battery in the vehicle of the present embodiment is not particularly limited. For example, when the secondary battery is mounted in a car, the secondary battery can be mounted in the engine room of the vehicle, behind the vehicle body, or under the seat.

[0162] Example

[0163] The following examples are given to more specifically illustrate the present invention. The present invention is not limited to the following examples unless it exceeds its purport. In addition, unless otherwise specified, "parts" represent "parts by mass" and "%" represents "% by mass". In addition, the amounts in the table are parts by mass, and are converted to non-volatile components except for the solvent. In addition, the blanks in the table represent that no mixing is performed.

[0164] The materials used in Examples and Comparative Examples are shown below.

[0165] <Dispersant>

[0166] Polyvinyl pyrrolidone (manufactured by Nippon Catalyst Co., Ltd., K-30, weight average molecular weight 40,000) was used as the dispersant (A).

[0167] Polyvinyl butyral resin (manufactured by Sekisui Chemical Co., Ltd., BL-10, weight average molecular weight 15,000) was used as the dispersant (B).

[0168] Hydrogenated nitrile rubber (dispersant 6 manufactured according to Japanese Patent No. 6933285) was used as the dispersant (C).

[0169] <Measurement of weight average molecular weight (Mw) of dispersant>

[0170] The weight average molecular weight (Mw) of the dispersant is measured by gel permeation chromatography (GPC) equipped with a refractive index (RI) detector. HLC-8320GPC (manufactured by Tosoh Co., Ltd.) is used as an apparatus, three separation columns are connected in series, and the fillers are "TSK-GELSUPER AW-4000", "AW-3000", and "AW-2500" manufactured by Tosoh Co., Ltd., respectively. 30mM triethylamine and 10mM LiBr N, N-dimethylformamide solution are used as eluents at an oven temperature of 40°C, and the measurement is carried out at a flow rate of 0.6mL / min. The concentration of the measured sample is adjusted to 1% using a solvent containing the eluent, and 20 microliters are injected. The weight average molecular weight is a polystyrene conversion value.

[0171] <Production of standard negative electrode>

[0172] In a 150 ml plastic container, 0.5 parts by mass of acetylene black (DENKA BLACK (registered trademark) HS-100, manufactured by DENKA), 1 part by mass of MAC500LC (carboxymethylcellulose sodium salt Sunrose special type MAC500L, manufactured by Nippon Paper Industries, non-volatile content 100%), and 98.4 parts by mass of water were added, and then stirred at 2000 rpm for 30 seconds using a rotation / revolution mixer (Thinky Defoaming Rentaro, ARE-310). Furthermore, 92 parts by mass of artificial graphite (Nippon Graphite Industries, CGB-20) and 5 parts by mass of silicon (silicon nanooxide SiO 1.3C 5μm, non-volatile content 100%, manufactured by Osaka Titanium Technologies) were added as active materials, and stirred at 3000 rpm for 10 minutes using a high-speed stirrer. Then, 3.1 parts by mass of styrene butadiene rubber (SBR) (TRD2001, manufactured by JSR) was added, and the mixture was stirred at 2000 rpm for 30 seconds using the rotation / revolution mixer to obtain a composite material slurry for the negative electrode. Then, a coating device was used to coat the electrode with a unit area weight of 8 mg / cm 2 After applying the negative electrode composite material slurry on the copper foil in a manner, the coating was dried in an electric oven at 120°C ± 5°C for 25 minutes. Then, a rolling process was performed using a roller press (manufactured by Thank-Metal Co., Ltd., 3t hydraulic roller press) to produce a composite material layer with a density of 1.6g / cm 3 The standard negative electrode.

[0173] 《Physical property measurement and evaluation methods》

[0174] The physical property measurement and evaluation methods of the carbon material, the carbon material dispersion composition, the electrode film, and the secondary battery used in each of the examples and comparative examples described below are as follows.

[0175] <BET specific surface area of ​​carbon materials>

[0176] 0.03 g of the carbon material was weighed using an electronic balance (Sartorius, MSA225S100DI) and then dried at 110° C. for 15 minutes while degassing. The BET specific surface area of ​​the carbon material was then measured using a fully automatic specific surface area measuring device (Mountech, HM-model 1208).

[0177] <Graphitization degree of carbon material (B / A ratio)>

[0178] The carbon material was placed in the concave part of the glass sample plate (outer diameter 5.0 cm × 3.5 cm, thickness 3 mm, sample part 2.0 cm × 2.0 cm, thickness 2 mm) and flattened using a glass slide. Then, a sample for powder X-ray diffraction analysis of the carbon material was set on a fully automatic multi-purpose X-ray diffraction device (SmartLab, Rigaku Co., Ltd.), and the operation was performed from 15° to 35° and analyzed. Sampling was performed in units of 0.01°, and the scanning speed was set to 1° / minute. The voltage was set to 40 kV, the current was set to 40 mA, and the X-ray source was set to CuKα rays. Regarding the two peak intensity ratios observed in the diffraction angle 2θ = 15° to 35° obtained at this time, the drawings appearing at the diffraction angle 2θ = 15° to 35° were respectively subjected to 11-point simple moving averages, and within the range of the diffraction angle 2θ = 20° to 30°, the peak intensity on the low angle side was set to A, and the peak intensity on the high angle side was set to B, and calculated as follows. At this time, the base line is a line connecting the plots of 2θ=16° and 2θ=34°. The degree of graphitization of the carbon material is calculated by the following formula 1.

[0179] (Formula 1) Graphitization degree of carbon material = B / A

[0180] The degree of graphitization (B / A ratio) of the carbon material was evaluated according to the following criteria.

[0181] α: 1.0 or more and less than 1.5

[0182] β: 1.5 or more and 2.5 or less

[0183] γ: more than 2.5

[0184] δ: less than 1.0

[0185] -: Peak value is one

[0186] <Carbon purity of carbon materials>

[0187] The carbon material was acid-decomposed using a microwave sample pretreatment device (Milestone-general, ETHOS 1) to extract the metals contained in the carbon material. The metal content (total amount of iron, cobalt, magnesium, aluminum, copper, nickel, zirconium oxide, and molybdenum) in the extract was then calculated using a composite ICP emission spectrophotometer (Agilent, 720-ES). The carbon purity (mass %) of the carbon material was calculated as follows.

[0188] Carbon purity of carbon material (mass %) = ((carbon material mass - metal amount) ÷ carbon material mass) × 100

[0189] <G / D ratio of carbon materials>

[0190] The carbon material was placed on a Raman microscope (XploRA, manufactured by Horiba, Ltd.) and the measurement was performed using a laser wavelength of 532 nm. The measurement conditions were set to an acquisition time of 60 seconds, a cumulative number of 2 times, a 10% light reduction filter, a magnification of 20 times for the objective lens, a confocal aperture of 500, a slit width of 100 μm, and a measurement wavelength of 100 cm. -1 ~3000cm -1 The carbon material for measurement was separated and taken out onto a glass slide and flattened using a spatula. Among the peaks obtained, the peak at 1560 cm in the spectrum -1 ~1600cm -1 The maximum peak intensity is set to G in the range of 1310 cm -1 ~1350cm -1 The maximum peak intensity within the range is set to D, and the ratio of G / D is set to the G / D ratio of the carbon material.

[0191] <Average outer diameter of carbon material>

[0192] Using an electronic balance (Sartorius, MSA225S100DI), 0.2 g of carbon material was weighed in a 450 mL SM sample bottle (manufactured by Sansho Co., Ltd.), 200 mL of toluene was added, and an ultrasonic homogenizer (Advanced Digital Sonifer (registered trademark), model (MODEL) 450DA, manufactured by BRANSON) was used to perform a dispersion treatment for 5 minutes under ice bath cooling with an amplitude of 30%, thereby adjusting the carbon material dispersion composition. Then, the carbon material dispersion composition was appropriately diluted, and a few μL was dripped in the form of a collodion film. After drying at room temperature, it was directly observed using a transmission electron microscope (H-7650, manufactured by Hitachi, Ltd.). The observation was performed by taking a plurality of photos containing more than 10 multilayer CNTs in the field of view at a magnification of 50,000 times, and the outer diameters of 300 multilayer CNTs randomly extracted from the photos were measured, and the average value was used as the average outer diameter (nm) of the carbon material.

[0193] <Volume resistivity of carbon materials>

[0194] Using a powder resistivity measuring device (Mitsubishi Chemical Analytech Co., Ltd.: Loresta GP Powder Resistivity Measuring System MCP-PD-51), the sample mass was set to 1.2 g, and a powder probe unit (four-probe-annular electrode, electrode spacing 5.0 mm, electrode radius 1.0 mm, sample radius 12.5 mm) was used. The applied voltage limiter was set to 90 V to measure the volume resistivity [Ω·cm] of the carbon material under various pressures. 1 g / cm was calculated. 3 The value of the volume resistivity of the carbon material at the density.

[0195] The conductivity of the carbon material was evaluated at 1.0 × 10 -2 Ω·cm or more and less than 2.0×10 -2 Ω·cm:++(excellent), 2.0×10 -2 Ω·cm or more and less than 3.0×10 -2 Ω·cm: +(good), 3.0×10 -2 Ω·cm or more: - (poor).

[0196] <Initial viscosity of carbon material dispersion composition>

[0197] After the carbon material dispersion composition was left to stand in a thermostatic chamber at 25°C for more than 1 hour, the carbon material dispersion composition was immediately subjected to a B-type viscometer with a rotor rotation speed of 6 rpm. A No. 3 rotor was used for the measurement. When the initial viscosity was less than 200 mPa·s, a No. 2 rotor was used.

[0198] The evaluation criteria for the initial viscosity are: 500 mPa·s or more and less than 5,000 mPa·s: ++ (excellent); 100 mPa·s or more and less than 500 mPa·s or 5,000 mPa·s or more and less than 10,000 mPa·s: + (good); less than 100 mPa·s or 10,000 mPa·s or more: - (poor)

[0199] <Thixotropy (TI value) of carbon material dispersion composition>

[0200] After the carbon material dispersion composition was allowed to stand in a thermostatic bath at 25° C. for 24 hours, the carbon material dispersion composition was fully stirred and then immediately subjected to a B-type viscometer rotor rotation speed of 6 rpm. Then, the B-type viscometer rotor was immediately subjected to a rotation speed of 60 rpm. At this time, when the viscosity measured at 6 rpm was defined as S and the viscosity measured at 60 rpm was defined as T, S / T was defined as the TI value.

[0201] The evaluation criteria of the TI value were 3 or more and less than 5: ++ (excellent), 2 or more and less than 3 or 5 or more and less than 7: + (good), and less than 2 or 7 or more: - (poor).

[0202] <Temporal stability of carbon material dispersion composition>

[0203] The carbon material dispersion composition was left to stand in a thermostatic bath at 60° C. for 7 days, then transferred to a thermostatic bath at 25° C. and left to stand until the CNT dispersion composition reached 25° C. Then, the viscosity was measured at a B-type viscometer rotor rotation speed of 6 rpm. A No. 3 rotor was used for the measurement.

[0204] The evaluation criteria for temporal stability were 2,000 mPa·s or more and 10,000 mPa·s or less: ++ (excellent), 500 mPa·s or more and less than 2,000 mPa·s or more than 10,000 mPa·s and less than 20,000 mPa·s: + (good), and less than 500 mPa·s or more than 20,000 mPa·s: - (poor).

[0205] <Volume resistivity of electrode film>

[0206] Use the applicator to make the weight per unit area of ​​the electrode 20 mg / cm 2 After applying the composite slurry on the aluminum foil in a manner, the coating was dried in an electric oven at 120°C ± 5°C for 25 minutes. Then, the surface resistivity (Ω / Υ) of the dried coating was measured using Loresta GP, MCP-T610 manufactured by Mitsubishi Chemical Analytech (stock company). After the measurement, multiply it by the thickness of the electrode composite layer formed on the aluminum foil to obtain the volume resistivity (Ω·cm) of the electrode film. The thickness of the electrode composite layer is the average value obtained by measuring 3 points in the electrode film using a film thickness meter (manufactured by NIKON, digital micrometer (DIGIMICRO) MH-15M) minus the thickness of the aluminum foil, as the volume resistivity (Ω·cm) of the electrode film.

[0207] The evaluation criteria of volume resistivity were set as less than 4 Ω·cm: ++ (excellent), 4 Ω·cm or more and less than 8 Ω·cm: + (good), and 8 Ω·cm or more: - (poor).

[0208] <Peel strength of electrode film>

[0209] Use an applicator to make the weight per unit area of ​​the electrode 20 mg / cm 2After the composite material slurry is applied on the aluminum foil in an electric oven, the coating is dried for 25 minutes at 120°C ± 5°C. Then, the coating direction is used as the major axis and cut into two 90mm×20mm rectangles. In the determination of peel strength, a desktop tensile tester (manufactured by Toyo Seiki Seisakusho, Strograph E3) is used to evaluate the 180-degree peel test method. Specifically, a 100mm×30mm double-sided tape (No.5000NS, manufactured by Nitoms (stock)) is attached to a stainless steel plate so that the prepared battery electrode composite material layer is closely attached to the other side of the double-sided tape, and the stripping is performed while being stretched from bottom to top at a certain speed (50mm / minute), and the average value of the stress at this time is used as the peel strength.

[0210] The evaluation criteria of the peel strength were 0.7 N / cm or more: ++ (excellent), 0.5 N / cm or more and less than 0.7 N / cm: + (good), and less than 0.5 N / cm: - (poor).

[0211] <Evaluation of rate characteristics of lithium-ion secondary batteries>

[0212] The laminated lithium-ion secondary battery was placed in a constant temperature room at 25°C, and a charge and discharge device (manufactured by Hokuto Electric Co., Ltd., SM-8) was used for charge and discharge measurement. After constant current and constant voltage charging (cutoff current 1.0mA (0.02C)) at a charge end voltage of 4.2V at a charging current of 10mA (0.2C), constant current discharge was performed at a discharge current of 10mA (0.2C) with a discharge end voltage of 2.5V. After repeating the above operation three times, constant current and constant voltage charging (cutoff current (1.0mA and 0.02C)) was performed at a charge current of 10mA (0.2C) with a charge end voltage of 4.2V, and constant current discharge was performed at a discharge current of 0.2C and a discharge current of 3C until the discharge end voltage reached 2.5V, and the discharge capacity was calculated respectively. The rate characteristics can be expressed by the ratio of the 0.2C discharge capacity to the 3C discharge capacity and the following formula 2.

[0213] (Equation 2) Rate characteristics = 3C discharge capacity / third 0.2C discharge capacity × 100 (%)

[0214] Regarding the evaluation of rate characteristics, the rate characteristics of 80% or more were set as +++ (excellent), 70% or more and less than 80% were set as ++ (good), 60% or more and less than 70% were set as + (acceptable), and less than 60% were set as - (poor). Regarding the cycle characteristics, the cycle characteristics of 90% or more were set as +++ (excellent), 85% or more and less than 90% were set as ++ (good), 80% or more and less than 85% were set as + (acceptable), and less than 80% were set as - (poor).

[0215] <Evaluation of cycle characteristics of lithium-ion secondary batteries>

[0216] The laminated lithium-ion secondary battery was placed in a constant temperature room at 25°C, and a charge and discharge device (manufactured by Hokuto Electric Co., Ltd., SM-8) was used for charge and discharge measurements. At a charging current of 50mA (1C), constant current and constant voltage charging was performed with a charge termination voltage of 4.2V (cut-off current 1.25mA (0.025C)), and constant current discharge was performed at a discharge current of 50mA (1C) with a discharge termination voltage of 2.5V. The above operation was repeated 200 times. 1C is set as the current value at which the theoretical capacity of the positive electrode is discharged within 1 hour. The cycle characteristics can be expressed by the ratio of the third 1C discharge capacity to the 200th 1C discharge capacity at 25°C, and the following formula 3.

[0217] (Formula 3) Cycle characteristics = 1C discharge capacity at the third time / 1C discharge capacity at the 200th time × 100 (%)

[0218] Regarding the cycle characteristics evaluation, a cycle characteristic of 90% or more was rated as +++ (excellent), 85% or more and less than 90% was rated as ++ (good), 80% or more and less than 85% was rated as + (acceptable), and less than 80% was rated as - (poor).

[0219] (Example 1-1)

[0220] 10 kg of carbon material (multilayer CNT, manufactured by JEIO, JENOTUBE 6A) is weighed in a 120 L heat-resistant container, and the heat-resistant container containing the carbon material is placed in a furnace. Then, nitrogen is introduced into the furnace to maintain a positive pressure while exhausting the air in the furnace. After the oxygen concentration in the furnace reaches less than 0.1%, it takes 30 hours to heat to 1400°C. While maintaining the temperature in the furnace at 1400°C, chlorine is introduced at a rate of 50 L / min for 100 hours. Then, nitrogen is introduced at 50 L / min and cooled while maintaining a positive pressure to obtain a carbon material (A) containing multilayer carbon nanotubes.

[0221] (Examples 1-2 to 1-4), (Comparative Examples 1-1 to 1-2)

[0222] Carbon materials (B) to (F) containing multiwalled carbon nanotubes were obtained in the same manner as in Example 1-1 except that the temperature in the furnace was changed to the temperature described in Table 1.

[0223] (Comparative Examples 1-3 to 1-5)

[0224] The carbon material (multilayer CNT, manufactured by KUMHO PETROCHEMICAL, 100T) is referred to as the carbon material (G), the carbon material (multilayer CNT, manufactured by Nanocyl, NC7000) is referred to as the carbon material (H), and the carbon material (multilayer CNT, manufactured by JEIO, JENOTUBE 6A) is referred to as the carbon material (I). The carbon material (G) contains 3000 ppm of iron and 1500 ppm of cobalt, the carbon material (H) contains 11000 ppm of iron and 3000 ppm of cobalt, and the carbon material (I) contains 4000 ppm of iron and 2000 ppm of cobalt.

[0225] (Comparative Examples 1-6 to 1-9)

[0226] The purified CNT (C) in Japanese Patent No. 6586197 is referred to as carbon material (J), the CNT (F) in Japanese Patent No. 6590034 is referred to as carbon material (K), the CNT (G) in Japanese Patent No. 6590034 is referred to as carbon material (L), and the CNT (D) in Japanese Patent No. 6801806 is referred to as carbon material (M).

[0227] (Comparative Examples 1-10)

[0228] CNT (N) was obtained by the same method as in Example 1-1 except that the carbon material (CNT, manufactured by JEIO, JENOTUBE 6A) was changed to CNT (manufactured by Nanocyl, NC7000).

[0229] Evaluation results of CNTs produced in Examples 1-1 to 1-4 and Comparative Examples 1-1 to 1-10 are shown in Table 1. All carbon materials in Examples have two peaks in the range of diffraction angle 2θ = 24.0° to 27.0°, while Comparative Examples 1-3 to 1-5, 1-7, and 1-9 have only one peak.

[0230]

[0231] (Example 2-1)

[0232] 95.5 parts of N-methyl-2-pyrrolidone (NMP) and 1.5 parts by mass of a dispersant (A) (polyvinyl pyrrolidone (manufactured by Nippon Catalyst Co., Ltd., K-30, weight average molecular weight 40,000)) were added to a stainless steel container, and stirred with a disperser until uniform. Then, 3.0 parts by mass of the carbon material (A) was added while stirring with a disperser, and a square hole high shear mesh was assembled on a high shear mixer (L5M-A, manufactured by SILVERSON), and the whole was made uniform at a speed of 8,600 rpm, and a grind gauge was used to perform batch dispersion until the dispersed particle size became 250 μm or less. Next, the contents of the stainless steel container are fed and passed through a bead mill filled with zirconia beads having a diameter of 1.0 mm φ (DYNO-MILL Multi-functional Laboratory, manufactured by SHINMARU ENTERPRISES) for a 10-minute cyclic dispersion treatment. Subsequently, the dispersed liquid is supplied to the high-pressure homogenizer via a pipe and 15 passes through the dispersion treatment. The dispersion treatment is performed using a single nozzle chamber at a nozzle diameter of 0.25 mm and a pressure of 100 MPa, and then passed through a nylon mesh having a pore size of 20 μm through a magnetic filter having a surface magnetic flux density of 17,000 Gauss to obtain a carbon material dispersion composition (A1) containing 3.0 parts by mass of carbon material (A).

[0233] (Examples 2-2 to 2-12), (Comparative Examples 2-1 to 2-10)

[0234] Except for changing the carbon material, dispersant and dispersion conditions described in Table 2, the carbon material dispersion compositions (A2) to (N1) of (Example 2-2) to (Comparative Example 2-12) were obtained in the same manner.

[0235] Table 2 shows the evaluation results of the dispersion compositions prepared in (Examples 2-1 to 2-12) and (Comparative Examples 2-1 to 2-10).

[0236]

[0237] (Example 2-13)

[0238] <Production of single-walled carbon nanotube dispersion composition (S1)>

[0239] 97.6 parts of NMP were added to a stainless steel container, and 2.0 parts of polyvinylidene fluoride resin (Solef 5130 manufactured by Solvay) was added while stirring with a disperser, and the mixture was stirred with a disperser until Solef 5130 was dissolved. Then, 0.4 parts of single-walled carbon nanotubes (TUBALL manufactured by OCSiAl, carbon purity 93%) were weighed and added while stirring with a disperser, and a square-hole high-shear mesh was installed on a high-shear mixer (L5M-A manufactured by Silverson), and batch dispersion was performed at a speed of 8,600 rpm until the entire mixture became uniform. Then, the dispersed liquid was supplied from the stainless steel container via a pipe to a high pressure homogenizer (Star Burst Labo HJP-17007, manufactured by SUGINO MACHINE) and the dispersion treatment was performed 5 times to obtain a single-walled carbon nanotube dispersed composition (S1). The dispersion treatment was performed using a single nozzle chamber with a nozzle diameter of 0.25 mm and a pressure of 60 MPa.

[0240] The BET specific surface area of ​​a single-walled carbon nanotube (TUBALL: manufactured by OCSiAl, carbon purity 93%) is 975 m 2 / g.

[0241] <Production of Carbon Material Dispersed Composition>

[0242] Next, 33.3 parts of the dispersion composition (A1) prepared in Example 2-1 and 24 parts of NMP were added to 66.7 parts of the single-walled carbon nanotube dispersion composition (S1), and stirred with a disperser until uniform, thereby obtaining a dispersion composition (A1S1-1). The solid content of the dispersion composition (A1S1-1) was 2.5%.

[0243] (Example 2-14)

[0244] A carbon material dispersion composition (A1S1-2) was obtained by the same method as in Example 2-13 except that 50 parts of the single-walled carbon nanotube dispersion composition (S1) was used instead of 66.7 parts of the single-walled carbon nanotube dispersion composition (S1), 50 parts of the carbon material dispersion composition (A1) was used instead of 33.3 parts of the carbon material dispersion composition (A1), and 18 parts of NMP was used instead of 24 parts of NMP. The solid content of the carbon material dispersion composition (A1S1-2) was 2.5%.

[0245] (Example 2-15)

[0246] A carbon material dispersion composition (A1S1-3) was obtained by the same method as in Example 2-13 except that 33.3 parts of the single-walled carbon nanotube dispersion composition (S1) was used instead of 66.7 parts of the single-walled carbon nanotube dispersion composition (S1), 66.7 parts of the carbon material dispersion composition (A1) was used instead of 33.3 parts of the carbon material dispersion composition (A1), and 52 parts of NMP was used instead of 24 parts of NMP. The solid content of the carbon material dispersion composition (A1S1-3) was 2.5%.

[0247] (Example 2-16)

[0248] A carbon material dispersion composition (A1S1-4) was obtained by the same method as in Example 2-13 except that 20 parts of the single-walled carbon nanotube dispersion composition (S1) was used instead of 66.7 parts of the single-walled carbon nanotube dispersion composition (S1), 80 parts of the carbon material dispersion composition (A1) was used instead of 33.3 parts of the carbon material dispersion composition (A1), and 63 parts of NMP was used instead of 24 parts of NMP. The solid content of the carbon material dispersion composition (A1S1-4) was 2.5%.

[0249] Table 3 shows the evaluation results of the dispersion compositions prepared in Examples 2-13 to 2-16.

[0250]

[0251] (Example 3-1)

[0252] Capacity 150cm 3 6.3 parts by mass of NMP solution and 20 parts by mass of NMP were weighed in a plastic container in which 8% by mass of PVDF (polyvinylidene fluoride, manufactured by Solvey, Solef #5130) was dissolved. Then, 8.3 parts by mass of the carbon material dispersion composition (A1) was added, and a self-rotation / revolution mixer (degassing Rentaro, ARE-310) was used to stir at 2000 rpm for 30 seconds. Furthermore, 98.7 parts by mass of the positive electrode active material (manufactured by BASF TODA Battery Materials Co., Ltd., HED (registered trademark) NCM-111 1100) was added, and a self-rotation / revolution mixer (degassing Rentaro, ARE-310) was used to stir at 2000 rpm for 2.5 minutes to obtain a composite slurry (A1).

[0253] Then, the applicator was used to apply the electrode at a weight per unit area of ​​20 mg / cm 2After applying the composite material slurry (A1) on aluminum foil in a manner, the coating was dried in an electric oven at 120°C ± 5°C for 25 minutes to obtain an electrode film (A1). Then, the electrode film (A1) was rolled using a roller press (manufactured by Thank-Metal, 3t hydraulic roller press) to obtain a positive electrode (A1). In addition, the unit area weight of each unit of the composite material layer was 20 mg / cm 2 The density of the composite material layer after calendering is set to 3.1 g / cc.

[0254] (Example 3-2 to Example 3-16), (Comparative Examples 3-1 to 3-10)

[0255] As described in Table 4, synthetic material slurries (A2) to (N1) were obtained by the same method as that for producing the synthetic material slurry (A1), except that the dispersion compositions (A2) to (N1) were used instead of the dispersion composition (A1).

[0256] Next, as shown in Table 4, electrode films (A2) to (N1) and positive electrodes (A2) to (N1) were produced by the same method as that for producing the positive electrode (A1), except that the composite material slurry (A1) was changed to composite material slurries (A2) to (N1).

[0257] Table 4 shows the evaluation results of the electrode films produced in (Examples 3-1 to 3-16) and (Comparative Examples 3-1 to 3-10).

[0258] [Table 4]

[0259] Table 4.

[0260]

[0261] (Example 4-1)

[0262] The positive electrode (A1) and the standard negative electrode were punched into 45 mm × 40 mm and 50 mm × 45 mm, respectively, and inserted into an aluminum laminate bag together with a separator (porous polypropylene film) inserted therebetween, and dried in an electric oven at 60°C for 1 hour. Then, 2 mL of an electrolyte solution (a mixed solvent made by mixing ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in a ratio of 1:1:1 (volume ratio) was injected into a glove box filled with argon gas, and 2 parts by mass of vinylene carbonate (VC) was added to 100 parts by mass of the mixed solvent as an additive) was added to the LiPF 6 After dissolving in a non-aqueous electrolyte solution at a concentration of 1 M), the opening was sealed with an aluminum laminate to produce a laminated lithium ion secondary battery (A1).

[0263] (Example 4-2 to Example 4-16), (Comparative Example 4-1 to Comparative Example 4-10)

[0264] Laminated lithium ion secondary batteries (A2) to (N1) were prepared by the same method as that for the laminated lithium ion secondary battery (A1) except that the positive electrode was changed to the one described in Table 5.

[0265] Table 5 shows the evaluation results of the lithium ion secondary batteries produced in (Example 4-1 to Example 4-16) and (Comparative Example 4-1 to Comparative Example 4-10).

[0266] [Table 5]

[0267] Table 5.

[0268]

[0269] In the embodiment described, the BET specific surface area of ​​the carbon material used is 400 m 2 / g~650m 2 / g and in the powder X-ray diffraction analysis, a carbon material having two peaks in the range of diffraction angle 2θ=24.0°~27.0°. In the embodiment, compared with the comparative example, a lithium ion secondary battery having excellent stability over time of the carbon material dispersion composition, excellent volume resistivity and peel strength of the electrode film using the carbon material dispersion composition, and excellent rate characteristics and cycle characteristics is obtained. Therefore, it is obvious that the present invention can provide a lithium ion secondary battery with high capacity, high output and high durability that is difficult to achieve using existing carbon material dispersion compositions.

[0270] A vehicle equipped with the lithium ion secondary battery of the present invention has high charge and discharge performance and excellent cycle characteristics, and therefore it has been confirmed that a vehicle having high safety and improved fuel efficiency can be obtained.

[0271] Although the present invention has been described above with reference to the embodiments, the present invention is not limited thereto and various modifications that can be understood by those skilled in the art can be made to the configuration and details of the present invention within the scope of the present invention.

[0272] The disclosure of this application is related to the subject matter described in Japanese Patent Application No. 2022-187584 filed on November 24, 2022, and all the disclosed contents are incorporated herein by reference.

Claims

1. A carbon material comprising multi-walled carbon nanotubes and satisfying the following (1) and (2), (1) The specific surface area of ​​the Buerte is 400m 2 / g~650m 2 / g, (2) In powder X-ray diffraction analysis, it has at least two peaks within the range of diffraction angle 2θ = 24.0° to 27.0°.

2. The carbon material according to claim 1, wherein In powder X-ray diffraction analysis, when the peak intensity on the low-angle side in the range of diffraction angle 2θ=24.0° to 27.0° is represented by A and the peak intensity on the high-angle side is represented by B, the B / A ratio is 1.0 to 2.

5.

3. The carbon material according to claim 1 or 2, wherein The carbon purity is 99.9 mass % or more.

4. The carbon material according to any one of claims 1 to 3, wherein When 1560 cm -1 ~1600cm -1 The maximum peak intensity in the range of 1310 cm is set as G, and the peak intensity at 1310 cm is set as -1 ~1350cm -1 When the maximum peak intensity in the range of is set to D, the G / D ratio is 1.0 to 4.

5. 5 . A carbon material dispersion composition comprising the carbon material according to claim 1 , a dispersant, and a dispersion medium.

6. The carbon material dispersion composition according to claim 5, wherein After the carbon material dispersion composition was prepared, the viscosity of the carbon material dispersion composition after being stored at 60°C for one week was measured using a Brookfield viscometer at 25°C and a rotor rotation speed of 6 rpm to be 500 to 20,000 mPa·s. 7 . The carbon material dispersion composition according to claim 5 , comprising a fluororesin. 8 . A composite material slurry comprising the carbon material dispersion composition according to claim 5 and an active substance.

9. An electrode membrane formed from the composite material slurry according to claim 8. 10 . A secondary battery comprising an electrode having the electrode film according to claim 9 and an electrolyte.

11. A vehicle comprising the secondary battery according to claim 10.

12. A method for producing a carbon material dispersion composition, comprising the steps of: mixing a carbon material dispersion composition (I) comprising a carbon material, a dispersant, and a dispersion medium, and a carbon material dispersion composition (II) comprising single-walled carbon nanotubes and a fluororesin (except for the carbon material dispersion composition (I)); The carbon material is a carbon material comprising multi-walled carbon nanotubes and satisfying the following (1) and (2), (1) The specific surface area of ​​the Buerte is 400m 2 / g~650m 2 / g, (2) In powder X-ray diffraction analysis, it has at least two peaks within the range of diffraction angle 2θ = 24.0° to 27.0°.

Citation Information

Patent Citations

  • Conductive material dispersion liquid, electrode paste, and conductive material coating active substance

    JP2011070908A

  • Information processing device, information processing system, information processing method, and program

    JP2022187584A